2000
DOI: 10.3201/eid0602.009918
|View full text |Cite
|
Sign up to set email alerts
|

Norwalk-Like Viral Gastroenteritis Outbreak in U.S. Army Trainees

Abstract: An outbreak of acute gastroenteritis hospitalized 99 (12%) of 835 U. S. Army trainees at Fort Bliss, El Paso, Texas, from August 27 to September 1, 1998. Reverse transcriptase polymerase chain reaction tests for Norwalk-like virus were positive for genogroup 2. Gastroenteritis was associated with one post dining facility and with soft drinks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 13 publications
2
20
1
1
Order By: Relevance
“…1 Unpublished data obtained using VLP reagents. 2 Previous results using HV VLPs alone showed no binding to any carbohydrates tested (27), whereas results from this study demonstrated slight binding of VLPs to Le b , but only in the presence of stool extract. 3 Observation made by Hutson et al using baculovirus-expressed recombinant NV VLPs (33).…”
Section: Figurecontrasting
confidence: 49%
See 1 more Smart Citation
“…1 Unpublished data obtained using VLP reagents. 2 Previous results using HV VLPs alone showed no binding to any carbohydrates tested (27), whereas results from this study demonstrated slight binding of VLPs to Le b , but only in the presence of stool extract. 3 Observation made by Hutson et al using baculovirus-expressed recombinant NV VLPs (33).…”
Section: Figurecontrasting
confidence: 49%
“…Noroviruses are transmitted via ingestion of feces-contaminated water and food, exposure to aerosolized feces and vomitus, exposure to contaminated surfaces, and direct person-to-person contact, with disease symptoms including nausea, vomiting, and diarrhea. Outbreaks typically occur in areas of close human contact such as schools, day care centers, medical care facilities, cruise ships, and the military (2,10,22).…”
mentioning
confidence: 99%
“…Among 99 military trainees with norovirus infection, 88% had nausea, and 80% vomited, while 76% complained of abdominal pain, 67% had diarrhea, 47% had fever or chills, and 22% had headache (40). The temperature exceeded 100.4°F in 17% of subjects, while 17% had leukocytosis and 37% had thrombocytopenia.…”
Section: Figmentioning
confidence: 99%
“…Such outbreaks can occur in a variety of settings, affecting all ages, including child care centers, schools, restaurants, summer camps, hospitals, nursing homes, cruise ships, and military settings. NV outbreaks have been a serious problem in nursing homes for the elderly (3,10,21), on board large commercial cruise ships (11,30), and in military camps and battleships during deployment and wartime (1,2,15,36).…”
mentioning
confidence: 99%